Jumlah penduduk, tingkat pendidikan, dan pertumbuhan ekonomi dalam konteks kemiskinan di Kabupaten Kudus - Esabela, Soniya Erike; Rahmawaty, Ita (Nur Science Institute, 2024)
This study has the intent and purpose to test and understand how strong the influence of population, economic growth and education level is on the poverty rate in Kudus Regency in the period 2010-2023. This research uses a secondary quantitative approach. The data analysis used by the researcher is multiple linear regression. Based on the results of the study show that an increase in population tends to reduce the poverty rate. At the same time, economic growth has a positive and significant influence in reducing poverty in Kudus Regency. However, the education level variable does not have a significant influence. Based on these findings indicate that an increase in population and economic growth can contribute to reducing poverty. However, there needs to be support with efforts to improve the quality of human resources. Based on this study, it has limitations because it only uses secondary data that is aggregate.